Development of The Economic Potential of Kalisalak Kebasen Banyumas Village Based on Religious Moderation: (Companying Study With CBR Approach) - Dewi Laela Hilyatin; Miftaakhul Amri; Salma Labibah, Helmi; Akmussalamaah, Akrimah; Aisyati Sekar, Shofi (Amala Jurnal Pengabdian Kepada Masyarakat, 2024)
Kalisalak Village is known for its tourist villages and cultural traditions. The potential that is possessed, starting from the potential of natural resources developed as tourist destinations, the potential of MSMEs, and the potential of cultural traditions, can be integrated into a community's economic development based on religious moderation. One of them is the tradition of the Jamaican talisman. This community service is carried out as an effort to optimize the community's economic development based on religious moderation with the CBR (Community Based Research) approach through FGD, Sharing, and observation activities. There are five concepts or programs that are produced: pokdarwis and village government gather all relevant parties to develop programs; each stakeholder maps their potential and the problems they face; build networks or partnerships with external parties, namely academics, district-level government institutions, financial institutions, both bank and non- bank; some of the optimized programs are the integration of tourist destinations, MSME actors, and cultural tradition actors; The program is made in the form of a package, which is offered and promoted through online and offline strategies to government agencies, private sectors, and educational institutions.